Advances in Optical Waveguides - Nor Hafizah Ngajikin editor; Mohd. Rashidi Salim editor; Abu Sahmah Mohd. Supa'at author; Sevia Mahdaliza Idrus author; Abu Bakar Mohammad author; Ian Yulianti author; Abdulaziz Mohammed Ali Al-Hetar author; Norazan Mohd. Kassim author; Mohd. Haniff Ibrahim author; Suwasti Broto author; Kok Kia Sia author; Muhammad Yusof Mohd. Noor author; et al. (Skudai : Penerbit Universiti Teknologi Malaysia, 2008)
Includes bibliographical references and index